Fish Catch Rate and Fish Composition of Commercially Operated by Multi-Day Trawling off Sindhudurg Coast of Maharashtra, India - Kharatmol, B. R.; Sutar, V. B.; Kulkarni, A. S.; Markad, A. T.; Landage, A. T. (International Journal of Bio-resource and Stress Management, 2022)
The commercial-operated multi-day trawlers from Sindhudurg coast carried out fishing operations at Malvan landing center, South Konkan region, Maharashtra, India in the mean depth range of 18–31 m in September, 2016 to May, 2018 to assess the changing trends in the fish catch composition, catch and discards rate by multi-day trawlers operating along the Sindhudurg coast of Maharashtra state. The average catch rate was observed 25.03 kg h-1 and 31.72 kg h-1 with average discards 5.07 kg h-1 and 7.81 kg h-1 by multi-day trawler during 2016–17 and 2017–18 respectively. During two fishing seasons, the average catch rate was 28.37 kg h-1, with average discards of 6.44 kg h-1 by multi-day trawlers. Major catch composition of multiday trawlers comprised Arius maculatus, Parastromateus niger, Lactarius lactarius, Otolithes cuvieri, Lepturacanthus savala, Rastrelliger kanagurta, Scomberomorus guttatus, Cynoglossus macrostormus, Uroteuthis duvaucelii, and Penaeid prawns. Discards comprised juveniles of commercial species and adults of low market value fishes. Cod end mesh size of trawl net varied from 15–35 mm depending on the fishery resources harvested. Duration of fishing trips by multi-day trawlers varied from 2–4 days, peak fishing activities were observed during October to December followed by February in terms landing. The study clearly indicated an increase in the average catch rate h-1 trawler-1 during the year 2017–18 compared to the previous year 2016–17 along the Sindhudurg coast. The t-Test performed on fish catch and discard of multi-day trawlers showed a statistically significant difference (p<0.05) in a fish catch (kg h-1) and fish discards between two fishing seasons, i.e., 2016–17 and 2017–18.